Isolation and Molecular Identification of Indegenous Bacteria in Shell Waste of Blood Cockle from Kenjeran Beach, Surabaya - Marsyanda, Nadhifah; Isnawati; Muhaimin, Fitriari Izzatunnisa (LenteraBio : Berkala Ilmiah Biologi, 2024)
Chitinase is one of the existing compounds that is quite abundant in nature. Source of chitinase can be found in several species of bacteria with chitinolytic activity. Bacterial isolation was obtained from the shell of blood cockle (Tegillarca granosa) collected from around Kenjeran Beach, Surabaya, Indonesia. This study aims to identify superior chitinolytic bacteria in shell waste using a molecular identification method based on the 16S rRNA gene. Bacteria were isolated by bacterial culture on selective chitin media and a clear zone around the colony as an indicator of chitinolytic activity was measured. The molecular identification process was carried out using PCR (Polymerase Chain Reaction) and sequencing techniques. The sequencing results were analyzed in silico by phylogenetic tree reconstructions through the MEGA 11. The result were then analyzed by comparing similarity values and genetic distance between sequences. Eight chitinolytic bacteria were successfully obtained, of which two isolates from the coastal area were indicated to have the highest chitinolytic index of 0.50 and 0.71. Based on the results of the observation of colony morphology, molecular analysis using Basic Local Alignment Search Tools (BLAST), and phylogenetic tree reconstruction using the maximum likelihood (ML) method. The two isolates were identified as belonging to the genus Bacillus and Stenotrophomonas.